TELEMEDICINE AND RURAL HEALTHCARE ACCESS: A COMPARATIVE ANALYSIS OF EMERGING TECHNOLOGIES - Dr Ashwini L H; Dr Vinaykumar L H; Dr Hanumanaik L (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
The research examines the contributions of telemedicine to resolving issues regarding healthcare access in rural communities, which are isolated due to long distances between such communities and healthcare facilities, along with a lack of medical resources and other socio-economic problems. The research examines the effects of telemedicine on accessibility, patient satisfaction, and cost-effectiveness through a mixed methods approach that couples quantitative analysis of patient outcomes with qualitative interviews with rural healthcare providers and patients. Results show that telemedicine greatly reduces travel burdens, improves patient satisfaction, and maximizes healthcare costs, and hence is a promising solution to rural healthcare challenges. Barriers continue to exist, especially broadband limitations and uneven regulatory policies, preventing rural communities from realizing telemedicine’s full potential. Increasing the use of artificial intelligence, mobile health applications, blockchain, and other emerging technologies further boosts telemedicine by supporting predictive analytical functions, secure data management, and boosting patient and healthcare-provider interactions. The study contends that policy interventions should be put in place to expand broadband access and standardize telemedicine regulations to create a healthcare model that also provides equitable access for rural populations. The potential for telemedicine to address rural-urban health disparities and more positively impact the health of underserved communities is underscored by findings.